DESIGN ANDROID APPLICATION REMO PUTRI GAYA TAWI DANCE FOR VOCATIONAL STUDENTS - Hayati, Ainin Nurul; Yanuartuti, Setyo; Suryandoko, Welly (PEDAGOGIK : JURNAL PENDIDIKAN, 2023)
The utilization of digital technology in the independent curriculum with a Project Based Learning model is considered highly beneficial in implementing learning in schools. One of the uses of technology is through the use of an Android application as a medium for learning the Tari Remo Putri Gaya Tawi dance. This research aims to develop Android application-based learning media in learning Remo Putri Gaya Tawi Dance at SMK. This research uses R&D (Research and Development) method with Thiagarajan 4D model (define, design, develop, and disseminate). This research produces a definition in the form of the needs of teachers, students and the learning environment with an android application to support learning in the classroom and independent learning activities outside of school. The android design of the application in remo dance learning places interactive learning knowledge and skills of Tawi style princess remo dance based on 4 kinds of Tawi style princess remo movements and collaborates with project based learning syntax fosters student activity, interest, creativity and understanding so that mastery of the material both in practice and theory becomes very good i.e. 4.5, 4.7, and 4.8. Development obtained the form and the results of the  trial on the  teacher's response got an  average aspect of  79.65% got good criteria  with the aspect that obtained the highest percentage score was the content of the material of 82.14% which got very good criteria.